2021
DOI: 10.1093/mnras/stab3599
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar interferometry: precise curvature measurement from pulsar secondary spectra

Abstract: The parabolic structure of the secondary or conjugate spectra of pulsars is often the result of isolated one-dimensional (or at least highly anisotropic) lenses in the ISM. The curvature of these features contains information about the velocities of the Earth, ISM, and pulsar along the primary axis of the lens. As a result, measuring variations in the curvature over the course of a year, or the orbital period for pulsars in binaries, can constrain properties of the screen and pulsar. In particular the pulsar d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Note that our weighting is the same as the Jacobian of the transformation to "normalized Doppler profiles" as used in curvature estimation by Reardon et al (2020), which does not assume one-dimensional scattering. It differs from the theta-theta mapping method of Baker et al (2022), which is based on one-dimensional scattering.…”
Section: Methodology For Estimating Arc Curvaturementioning
confidence: 99%
See 1 more Smart Citation
“…Note that our weighting is the same as the Jacobian of the transformation to "normalized Doppler profiles" as used in curvature estimation by Reardon et al (2020), which does not assume one-dimensional scattering. It differs from the theta-theta mapping method of Baker et al (2022), which is based on one-dimensional scattering.…”
Section: Methodology For Estimating Arc Curvaturementioning
confidence: 99%
“…Much of this work was inspired by the remarkable interferometric study of PSR B0834+06 by Brisken et al (2010), and work on interstellar holography (Walker & Stinebring 2005;Walker et al 2008) laid important groundwork, too. Among other highlights in this scintillometry effort are several studies of binary pulsars (Rickett et al 2014;Main et al 2020;Mall et al 2022), the detection of scattering from a supernova remnant around a pulsar (Yao et al 2021), the location of multiple scattering screens toward nearby pulsars (Chen et al 2022;McKee et al 2022), and important new theoretical work (Simard et al 2019a(Simard et al , 2019bSprenger et al 2021;Shi & Xu 2021;Baker et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work was inspired by the remarkable interferometric study of PSR B0834+06 by Brisken et al (2010), and work on interstellar holography (Walker & Stinebring 2005;Walker et al 2008) laid important groundwork, too. Among other highlights in this scintillometry effort are several studies of binary pulsars (Rickett et al 2014;Main et al 2020;Mall et al 2022), the detection of scattering from a supernova remnant around a pulsar (Yao et al 2021), the location of multiple scattering screens toward nearby pulsars (Chen et al 2022;McKee et al 2022), and important new theoretical work (Simard et al 2019a,b;Sprenger et al 2021;Shi & Xu 2021;Baker et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…5. However, we found that the method of finding the curvature belonging to the strongest possible eigenvector as described in Baker et al (2022) deviated systematically from measurements done with the manual method described above. This deviation is strongest when the secondary spectra show reappearing stripes in addition to the arclets.…”
Section: Strong Scatteringmentioning
confidence: 64%